Understanding ureteroscopy complications according to modified Clavien classification system - Bin Shaheen, Usama; Ahmed Mahar, Naveed; Mughal, Nazish; Qureshi, Harris Hassan; Akhter, Naseem; Kalwar, Sara Rasheed (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the complications of ureteric stone treatment with semi-rigid uretero-renoscopy in accordance with the modified Clavien classification system. Method: The descriptive, prospective study was conducted at the Department of Urology, Sindh Institute of Urology and Transplantation, Karachi, from June 30, 2020, to December 29, 2021, and comprised patients of either gender aged 18-70 years having ureteric stones. All patients were subjected to ureterorenoscopy using a semi-rigid ureteroscope under general anaesthesia. The patients were followed up for 2 months. All complications were noted and graded in line with the Modified Clavien Complication System. Ultrasound and X-ray were used to determine the stone-free rate. Data was analysed using SPSS 23. Results: Of the 414 patients, 304(73.4%) were males and 110(26.5%) were females. The overall mean age was 40.22±13.10 years. There were 106(25.6%) proximal, 134(32.3%) middle, and 174(42%) distal ureteric stones. Stent placement was done in 56(13.5%) cases. There were 260(62.8%) patients with no complication, 90(21.7%) with grade I complications, 34(8.2%) with grade II complications, 10(2.4%) with grade IIIa, 8(1.9%) with grade IIIb, and 12 (2.9%) with grade IVa complications. Conclusion: Uretero-renoscopy was found to be a safe procedure, as it had minimal associated complications with optimal stone clearance and great dexterity. The Modified Clavien classification system was found to be an easy way to classify surgical complications of uretero-renoscopy. Key Words: Ureteroscopy, Modified Clavien classification system, Ureteric calculi, ESWL.